A Model of Basic Dental Care Service for Iran - Bayat, Fariborz; Ghasemi, Hadei (Journal of Dental School, 2019)
Objectives To study components of oral health care system in some developed countries and propose a model for Iran. Methods The present study was a qualitative, cross-sectional, and comparative research that took place in 2012. Oral health care systems in some developed countries have been reviewed to propose a framework for Iran. This framework has been discussed and reviewed by an expert panel using Delphi method. Results A table presenting type of service provider, type of centers and personnel, and methods for reimbursement in oral health care delivery system has been discussed by an expert panel. The experts, with an average 75% agreement rate, agreed on the need for a basic oral health care package free of charge for under 18-year-olds, compulsory periodical check-up examinations, and guarantee for payment of the services by national insurance funds. Simplicity, comprehensiveness, focus on prevention and at risk age groups facilitate the adaptability of the model to various populations. Conclusion An appropriate model for oral healthcare delivery system needs universal health insurance coverage, a basic service package focusing on preventive care with mandatory regular dental check-ups, participating of private practitioners, and financing services through government revenues, premium, and health tax.